SCIENCE AND TECHNOLOGY OF THE FUTURE - Kishor, B (Prof. B. Kishor, 2019)
United Nations Organization says: For the next 10 years we must focus on education for sustainable development. Development that meets the needs of the present without compromising the ability of future generations to meet their own needs is sustainable. It includes aspects such as peace, environmental integrity and human rights, and requires us to reassess our concept of “progress”. The U.N. Earth Charter says, “…… it is imperative that we, the peoples of Earth, declare our responsibility to one another, to the greater community of life and to future generations”. To achieve sustainability, we will have to draw from the richest veins of human wisdom, both past and present. Our survival hinges on realizing a profound change within human beings themselves. Only orientation in the inner life of humanity will enable us to meet the daunting challenges that face us. To achieve this, education needs on enhancing and strengthing the following human capacities: The wisdom to perceive the interconnectedness of life and living; the courage not to fearor deny difference, but to respect and strive to understand people of different cultures, and to grow from encounters with them; the compassion to maintain an imaginative empathy that reaches beyond one’s immediate surroundings and extends to those suffering in distant places.
Indian model of Science & Technology
Keywords: SCIENCE AND TECHNOLOGY; FUTURE; SCIENCE AND TECHNOLOGY OF THE FUTURE